Thermostable Serine Protease By Aspergillus parasiticus TEM Have Promising Activity In Enzymatic Dehairing Process - Behzat Oral Bıtlıslı; Bilge Hilal Cadirci; Huseyin ATA Karavana; Ihsan Yasa (Journal of New Results in Science)
In the present study, Aspergillus parasiticus TEM obtained from our culture collection produced appreciable quantities (2955.739.4 U/gds) of extracellular protease, but negligible quantities of keratinase, when grown on wheat bran moistened to 75% with Czapex Dox solution containing 1% NaNO3 by means of solid-state fermentation (SSF). After incubation at 27C for 3 days, A. parasiticus TEM reached to a maximum protease activity. The optimum pH of purified enzyme was around pH 8.0 at 30C, but substantial activity was recorded at the pH 7.0-11.0 and it is stable pH values ranging from 7.0-9.0 for 8 hours. Temperature optimum of the enzyme was found to be at 50 oC without Ca++ and to be highly stable (90%) at 30oC for 8 hours. When the protease from A. parasiticus TEM was used in dehairing process of cattle hide, the mixture of 100% crude enzyme, 1.5% lime and 1% sodium sulphide based on hide weight was completely dehaired hides at 30oC for 6 hours, but crude enzyme 200% alone carried out this process for 8 hours